REFORMASI BIROKRASI PADA KUA - Syahrudin, Syahrudin; Julaeha, Julaeha (Jurnal Bimas Islam, 2015)
Abstraksi Reformasi Birokrasi merupakan amanat UU, yang mana ditegaskan bahwa birokrasi harus dijalankan secara professional, transparan dan akuntabel. Kantor Urusan Agama (KUA) sebagai institusi di bawah Kementerian Agama dituntut melakukan reformasi birokrasi dalam memberikan pelayanan prima kepada masyarakat. Sejak tahun 2013, telah terbit berbagai langkah kongkrit upaya reformasi birokrasi pada KUA. Hasilnya, kini perlahan tapi pasti tingkat kualitas pelayanan KUA telah meningkat dan memuaskan publik.   Abstract Bureaucratic reforms are mandated by the law, which affirmed that the bureaucracy should be run in a professional, transparent and accountable. Religious Affairs Office (KUA) as an institution under the Ministry of Religious Affairs required to have bureaucratic reform in providing excellent service to the community. Since 2013, has published various concrete steps as bureaucratic reform efforts at Religious Affairs Office. As the result, now slowly but sure Religious Affairs Office level of service quality has improved and satisfy the public. Keywords: Reform, Bureaucracy, Excellent Service